Synthesis and mechanical properties of nanohydroxyapatite from egg shells and effects of nanoHA-titanium composite using microwave technique / Ainaa Zafirah Omar Arawi - Omar Arawi, Ainaa Zafirah (2015)
Hydroxyapatite (Caio (PO4 ) 6 (OH) 2,), is an interesting material of an inorganic compound whose chemical composition and crystallographic structures are similar to the composition of the bone. However, due to its poor mechanical properties, HA ceramics cannot be used for heavy load bearing applications. Natural source such as egg shells was composed by 94 wt. % of calcium carbonate (CaCO.i), which can be changed to calcium oxide (CaO) by calcinations process. The temperature and the duration to produced CaO was 900 °C for 2 hours. The synthesis of nano-HA was done by the mixtures of diammonium phosphate (DAP) and calcium hydroxide (CA (OH) 2) and subjected to heat using microwave for 30 minutes at 1100 W irradiation power. The X-Ray Diffraction (XRD) was used to characterize the phase and crystal sizes. As the results, nano-HA gave the highest peak that obtained clearly at 20-31.94 0 and located at (2/7) lattice. The nano- HA powder showed well defined broad crystalline peak. The crystalline size of nano-HA was in the range of 35 - 39 nm. Ball milled machine was used to mixed the nano-HA with different compositions of titanium (Ti) powder which were 10, 15, 20 and 25 wt.%. for 30 minutes and then was pressed by hand hydraulic pump with the force of 2300 psi to form the pellets. The pallets then were sintered at 1200 °C by the heating rate of 3 °C/min for 2 hours. Hardness, compression and wear test were tested. As a result, HA-25wt. %Ti composite gave the highest hardness test, 89.6 Hv, compressive test, 82.5 MPa and coefficient of friction for wear test,0.76 ji.The microstructure analyses showed, nano-HA particles have a high tendency to agglomerate and formed the shape likes needle morphology. The addition of 25wt %Ti, showed the distribution of each element in the composition have well distributed by using EDS analyses